Research on Shear Strength Parameters of the Silty Fine Sand and the Rounded Gravel Layers in Nanning City - Liming Yang; Fan Yang; Qian Zhou; Guangbin Zhang (Advances in Civil Engineering)
The silty fine sand and rounded gravel layers are widely distributed in Nanning City, China. Due to the low clay content, the silty fine sand and rounded gravel layers are prone to disturbance during sampling and transportation, which affects the shear strength test results. The reasonable determination of their shear strength is significant and imperative to the project. The rail transit project in Nanning is under large-scale construction. This work obtained the shear strength of the silty fine sand and the rounded gravel layers by conducting laboratory tests on undisturbed samples from deep foundation pits, combined with large-scale direct shear in situ tests. In addition, geotechnical investigation reports for typical projects in Nanning City were compiled, and the test data for the silty fine sand and the rounded gravel layers were comparatively analyzed using the empirical value. The results show that the shear strength test values of the fine sand layer are consistent with the current standard empirical values, and empirical values can be used for reference. The shear strength test value of the rounded gravel layer has significantly improved compared to the current standard empirical value, with a cohesion (c) value of 0–6.8 kPa and an increase in internal friction angle (φ) of 0%–12.5%. It is recommended to determine the shear strength of the rounded gravel layer based on the actual situation.